High-Throughput Shotgun Metagenomics of Microbial Footprints Uncovers a Cocktail of Noxious Antibiotic Resistance Genes in the Winam Gulf of Lake Victoria, Kenya - Sandra Khatiebi; Kelvin Kiprotich; Zedekiah Onyando; John Mwaura; Clabe Wekesa; Celestine N. Chi; Chrispinus Mulambalah; Patrick Okoth (Journal of Tropical Medicine)
Conclusions: This study highlights that the Winam Gulf of Lake Victoria in Kenya harbors a diverse array of antibiotic-resistant genes, including those conferring multidrug resistance. These findings suggest that the Gulf could be serving as a reservoir for more antibiotic-resistant genes, posing potential risks to both human health and aquatic biodiversity. The insights gained from this research can guide policy development for managing antibiotic resistance in Kenya.